2004
DOI: 10.1086/380798
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex onCoxiella burnetiiInfection: Protective Role of 17β‐Estradiol

Abstract: Q fever is a zoonosis caused by Coxiella burnetii and recently has been recognized as a potential agent of bioterrorism. In Q fever, men are symptomatic more often than women, despite equal seroprevalence. We hypothesized that sex hormones play a role in the pathogenesis of C. burnetii infection. When C57/BL6 mice were injected with C. burnetii, bacteria load and granuloma numbers were lower in females than in males. Ovarectomized mice showed increased bacteria load in the spleen and the liver, similar to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
88
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(101 citation statements)
references
References 37 publications
11
88
0
2
Order By: Relevance
“…The main significant differences between these two groups are age and sex, with symptomatic patients being significantly older and more often men than asymptomatic or poorly symptomatic patients. This result confirms what has already been described in previous studies: age and sex are the two major determinants of clinical manifestations of C. burnetii primary infection, with older men being more frequently symptomatic than young women, pregnant women and children [2][3][4]. Moreover, the results of Van Loenhout et al confirm that there is no correlation between clinical manifestations of C. burnetii primary infection and the long-term consequences of the infection, with no significant difference in longterm health status between notified and non-notified patients [5].…”
Section: Moving From Q Fever To C Burnetii Infectionsupporting
confidence: 92%
“…The main significant differences between these two groups are age and sex, with symptomatic patients being significantly older and more often men than asymptomatic or poorly symptomatic patients. This result confirms what has already been described in previous studies: age and sex are the two major determinants of clinical manifestations of C. burnetii primary infection, with older men being more frequently symptomatic than young women, pregnant women and children [2][3][4]. Moreover, the results of Van Loenhout et al confirm that there is no correlation between clinical manifestations of C. burnetii primary infection and the long-term consequences of the infection, with no significant difference in longterm health status between notified and non-notified patients [5].…”
Section: Moving From Q Fever To C Burnetii Infectionsupporting
confidence: 92%
“…33,[43][44][45] In P. chabaudi infection, ovariectomized female mice exhibit reduced production of the cytokines IL-12 and IFN-γ, leading to increased susceptibility. 24 However, in our study, ovariectomy in female mice caused low peak parasitemia and contributed to resistance against B. microti infection.…”
Section: Discussionmentioning
confidence: 99%
“…9 This suggests that, after exposure to C burnetii, both genders are equally affected; however, men are frequently more symptomatic. 20,45 In studies with animal models, estrogen has proven to play a protective role, 46 a fact that might explain why this predominance in males only occurs after puberty. 47 Furthermore, the current study observed that the average number of days with symptoms preceding hospitalization was much inferior for men than for women, which leads us to speculate that women, even when symptomatic, appear to have less severe symptoms and as a result are less likely to present to the Emergency Room, or if they do go, they do so later than men.…”
Section: Discussionmentioning
confidence: 99%